2022
DOI: 10.1007/s13353-022-00730-y
|View full text |Cite
|
Sign up to set email alerts
|

In silico and in vitro analysis of the impact of single substitutions within EXO-motifs on Hsa-MiR-1246 intercellular transfer in breast cancer cell

Abstract: MiR-1246 has recently gained much attention and many studies have shown its oncogenic role in colorectal, breast, lung, and ovarian cancers. However, miR-1246 processing, stability, and mechanisms directing miR-1246 into neighbor cells remain still unclear. In this study, we aimed to determine the role of single-nucleotide substitutions within short exosome sorting motifs — so-called EXO-motifs: GGAG and GCAG present in miR-1246 sequence on its intracellular stability and extracellular transfer. We applied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…We then validated APE1-hnRNPA2B1 interplay in the regulation of miRNAs containing an EXO-motif (see Supplementary Figure S8 and Supplementary Tables 8 and 9). Comparing all the obtained results, we identified hsa-miR-1246 as: i) the only DEmiRNA, in all the cell lines we tested so far (12, 17), having EXO-motif occurrences in both the precursor and mature forms; ii) a possible interactor of RBPs, based on structural studies showing the presence of EXO-motifs in its sequence (54) and, iii) a highly-expressed ncRNA in EVs derived from many human cancer cell lines (55).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…We then validated APE1-hnRNPA2B1 interplay in the regulation of miRNAs containing an EXO-motif (see Supplementary Figure S8 and Supplementary Tables 8 and 9). Comparing all the obtained results, we identified hsa-miR-1246 as: i) the only DEmiRNA, in all the cell lines we tested so far (12, 17), having EXO-motif occurrences in both the precursor and mature forms; ii) a possible interactor of RBPs, based on structural studies showing the presence of EXO-motifs in its sequence (54) and, iii) a highly-expressed ncRNA in EVs derived from many human cancer cell lines (55).…”
Section: Resultsmentioning
confidence: 87%
“…As an exhaustive target, we characterized the interaction of APE1 with miR-1246, already explored in the sorting process within EVs (54) and for its paracrine role in tumor progression of different cancer types (55). miR-1246 has been found to be oncogenic in lung, cervical, liver, colorectal, breast, pancreatic and ovarian cancers through mechanisms regulating GSK3β, JAK/STAT, PI3K/AKT, RAF/MEK/ERK, Wnt/β-catenin, THBS2/ MMP and NOTCH2 pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, RNA-binding proteins (hnRNPU and SYNCRIP) were identified in regulating sorting mechanism of miRNAs into EVs [ 108 , 109 ]. And these exosome sorting motifs have been found to be important in modulating miRNA stability and its intracellular transfer [ 110 ]. Recently, it has been suggested that the packaging of mRNA and lncRNA into EVs not only impacts intracellular messaging between cells or organs, but also plays a role in transforming the transcriptome of the source cell [ 111 ].…”
Section: Loading Evs With Functional Luminal Cargomentioning
confidence: 99%
“…Cancer is one of the deadliest illnesses worldwide. The global disease burden in 2018 was estimated to be 18.1 million new malignant cases ( 1 ). In India, there were approximately 2.25 million recorded cases and over 784,000 deaths in the year 2020 as per the National Institute of Disease Avoidance and Research.…”
Section: Introductionmentioning
confidence: 99%